MEMORIES OF A MOUNTAIN LANDSCAPE: CROSSING THE ANDES IN LATE COLONIAL CHILE. - Vega Palma, Alejandra (Revista de Historia Social y de las Mentalidades, 2024)
In this article, we discuss the centuries- long heritage of cultural associations relating Andes Mountains in colonial Chile with notions of danger. Ideas of risk and menace are present in different texts describing mountain passages, related to death in abrupt cliffs and precipices or the possibility of freezing. These cultural marks were established in early sixteenth century Chile and theirs echoes can be pinpointed in different texts written along the eighteenth century. It is noted that, in some cases, these topics encounter the descriptions of the sublime.
Keywords: memory; mountains; Chile; danger